2020
DOI: 10.1111/apa.15422
|View full text |Cite
|
Sign up to set email alerts
|

Novel coronavirus infection (COVID‐19) in children younger than one year: A systematic review of symptoms, management and outcomes

Abstract: Aim The aim of this systematic review was to evaluate the clinical characteristics of COVID‐19 in neonates and children under one year of age. Methods A systematic literature review of the MEDLINE, PubMed, CINAHL, Embase and EBSCO databases was carried out for studies from January 1, 2020, to April 7, 2020. We included all papers that addressed clinical manifestations, laboratory results, imaging findings and outcomes in infants and neonates. Results Our search identified 77 peer‐reviewed papers, and 18 papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 32 publications
3
47
2
7
Order By: Relevance
“…We included 18 reviews in our analysis. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Characteristics of the included reviews are shown in table 1; all are freely available online (see online supplemental appendix table 2). All reviews were in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 18 reviews in our analysis. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Characteristics of the included reviews are shown in table 1; all are freely available online (see online supplemental appendix table 2). All reviews were in English.…”
Section: Resultsmentioning
confidence: 99%
“…No reviews specifically focused on symptoms or signs among community samples of infected children, and none compared symptoms in hospitalised compared with non-hospitalised children. One review included only studies of infants, 16 one included a comparison of symptoms in children with those in adults from China 26 and one examined only gastrointestinal symptoms. 28 One study provided descriptive data from included studies only and did not report pooled estimates of symptom prevalence.…”
Section: Resultsmentioning
confidence: 99%
“…Infants and neonates appeared to present severe disease more commonly, as 7% were admitted to the intensive care unit (ICU) and one infant died. 38 To summarize, the currently available data showed that the majority of children with COVID-19 had a normal WBC count, and that lymphopenia was rarer in children than in adults. Since lymphopenia appears to be associated with the severity of COVID-19 in adults, the absence of significant lymphopenia in children may be explained by the milder disease in this population.…”
Section: Raised Leukocyte and Neutrophil Counts Have Been Associatedmentioning
confidence: 90%
“…Coronavirus disease 2019 (COVID-19) is a major problem in public health in the world. [ 1 , 2 ] COVID-19 has spread throughout China and globally, as a pandemic. [ 3 , 4 ] Up to June, 2020, the number of infections arising to 869,0000 and cause 41, 0000 deaths all over the world.…”
Section: Introductionmentioning
confidence: 99%